Perkembangan Tafsir Al – Qur’an Di Era Kemerdekaan Indonesia: Dinamika, Tokoh Dan Metodologi - Fauziah Nur Ariza; Anita Putri Siregar; Nafis Hasibuan; Faris Naufal; M. Maulana Farhan (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
The development of Qur'anic interpretation in the modern era is a response to increasingly complex social, cultural, scientific, and technological changes. Interpretation no longer focuses solely on linguistic and legal explanations but is also directed toward addressing the problems of contemporary Muslims. This journal examines the dynamics of the development of Qur'anic interpretation in the modern era, encompassing the background to its emergence, the characteristics of modern interpretation, and the methods and styles of interpretation used by modern commentators. Furthermore, it discusses important figures who played a role in the development of modern interpretation and their contributions to Islamic thought. The discussion shows that modern interpretation tends to be contextual, rational, and thematic, emphasizing the relevance of Qur'anic teachings to the lives of modern society. Thus, Qur'anic interpretation in the modern era serves as a bridge between the revealed text and the realities of contemporary Muslim life.